2022
DOI: 10.1055/s-0040-1719917
|View full text |Cite
|
Sign up to set email alerts
|

Selective N2-Alkylation of 1H-Indazoles and 1H-Azaindazoles

Abstract: A general and selective procedure for the N2-alkylation of 1H-indazoles and 1H-azaindazoles is presented. Promoted by either trifluoromethanesulfonic acid or copper(II) triflate, diverse 1H-indazoles/azaindazoles are selectively alkylated with varied primary, secondary, and tertiary alkyl 2,2,2-trichloroacetimidates at the N2-nitrogen to afford the corresponding 2-alkyl-2H-indazoles/azaindazoles. Forty-one examples are included along with a discussion of reaction optimization, scope, and mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…With a scalable assembly method of indazole 16 in hand, the subsequent N -methylation was examined (Scheme C, top). Using trimethyloxonium tetrafluoroborate (Me 3 O·BF 4 , known as Meerwein’s reagent) gave the best result compared with other methylation reagents, such as methyl iodide, dimethyl sulfate, dimethyl carbonate, and methyl 2,2,2-trichloroacetimidate. , The present reaction conditions using Me 3 O·BF 4 could suppress the generation of side-products 19 and 20 to an acceptable level. It has been reported that the regioselectivity between two nitrogen atoms on the indazole depends on the nature of the alkylating reagents .…”
Section: Resultsmentioning
confidence: 87%
“…With a scalable assembly method of indazole 16 in hand, the subsequent N -methylation was examined (Scheme C, top). Using trimethyloxonium tetrafluoroborate (Me 3 O·BF 4 , known as Meerwein’s reagent) gave the best result compared with other methylation reagents, such as methyl iodide, dimethyl sulfate, dimethyl carbonate, and methyl 2,2,2-trichloroacetimidate. , The present reaction conditions using Me 3 O·BF 4 could suppress the generation of side-products 19 and 20 to an acceptable level. It has been reported that the regioselectivity between two nitrogen atoms on the indazole depends on the nature of the alkylating reagents .…”
Section: Resultsmentioning
confidence: 87%